1992
DOI: 10.1002/app.1992.070440922
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of 2‐(dimethlamino) ethyl methacrylate onto gamma irradiated polypropylene fabric

Abstract: SYNOPSISPolypropylene fabric was gamma pre-irradiated at doses of 1,2, and 3 Mrads. The irradiated fabric was grafted with an aqueous solution of 2-(dimethylamino) ethyl methacrylate. The graft yield was studied as a function of the different variable conditions such as storage time, monomer concentration ( 10-40%), reaction time, and temperature ( 50, 70,lOO"C). The grafted polypropylene was further quaternized with dimethyl sulphate or monochloroacetic acid. The grafted and quarternized fabrics were dyed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…However, we observed that the concentration of hydroperoxy groups remained unchanged when leaving the irradiated polymer for 24 h. Gawish et al reported that the graft yields on preirradiated polypropylene remained unaffected even after 5 days of storage of the irradiated samples. 18 Esters are known to react with potassium hydroxamate under mild conditions and form acylhydroxamic acids, (N-hydroxyacylamides) 11 :…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed that the concentration of hydroperoxy groups remained unchanged when leaving the irradiated polymer for 24 h. Gawish et al reported that the graft yields on preirradiated polypropylene remained unaffected even after 5 days of storage of the irradiated samples. 18 Esters are known to react with potassium hydroxamate under mild conditions and form acylhydroxamic acids, (N-hydroxyacylamides) 11 :…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a high local concentration of the monomer around the formed active sites resulted in a high grafting yield. 15,16 Effect of the inhibitor The addition of some inorganic salts to the reaction mixture was investigated in an attempt to minimize the homopolymerization and to optimize the grafting conditions. The concentration of these salts was kept constant at 0.5 wt %, and the results are given in Table II.…”
Section: Effect Of the Solventmentioning
confidence: 99%
“…Polypropylene (PP), one of the most available versatile polymers, faces many problems in blending and compounding owing to its hydrophobicity, especially lacking any reactive functional groups [1,2]. The grafting technique with reactive monomers onto PP has been widely used in the modification of PP to overcome these problems [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%